Flavonoids isolated from the South African weed Chromolaena odorata (Asteraceae) have pharmacological activity against uropathogens - Aitebiremen G. Omokhua-Uyi; Muna A. Abdalla; Carmen M. Leonard; Abimbola Aro; Osariyekemwen O. Uyi; Johannes Van Staden; Lyndy J. McGaw (BMC, 2020)
Abstract Background Urinary tract infections (UTIs) caused by opportunistic pathogens are among the leading health challenges globally. Most available treatment options are failing as a result of antibiotic resistance and adverse effects. Natural sources such as plants may serve as promising alternatives. Methods Compounds were isolated from the South African weed Chromolaena odorata through column chromatography. Purified compounds were tested for antimicrobial activity using the p-iodonitrotetrazolium chloride (INT) colorimetric method, against uropathogenic Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Aspergillus fumigatus and Cryptococcus neoformans. Anti-biofilm, anti-adhesion and metabolic inhibition activities were investigated against selected strains. Safety of the compounds was determined against Vero monkey kidney, C3A human liver and colon (Caco2) cells. Results Four compounds identified as pectolinaringenin (1), (±)-4',5,7-trimethoxy flavanone (2), 5-hydroxy-3,7,4'-trimethoxyflavone (3) and 3,5,7-trihydroxy-4'-methoxyflavone) (4) were isolated. Minimum inhibitory concentration (MIC) varied between 0.016 and 0.25 mg/mL. Compounds 2 and 3 showed promising antimicrobial activity against E. coli, S. aureus, K. pneumoniae, A. fumigatus and C. neoformans with MIC between 0.016 and 0.125 mg/mL, comparable to gentamicin, ciprofloxacin and amphotericin B used as positive controls. Compounds 2 and 3 showed good anti-biofilm and metabolic inhibition activities against E. coli and S. aureus but weak anti-adhesion activity against the organisms. Low toxicity with selectivity indexes between 1 and 12.625 were recorded with the compounds, indicating that the compounds were rather toxic to the microbial strains and not to the human and animal cells. Conclusion Pharmacological activities displayed by compounds 2 and 3 isolated from C. odorata and low toxicity recorded credits it as a potential lead for the development of useful prophylactic treatments and anti-infective drugs against UTIs. Although known compounds, this is the first time these compounds have been isolated from the South African weed C. odorata and tested for antimicrobial, anti-biofilm, metabolic inhibition and anti-adhesion activities.